The Three Pillars of Advanced Education - Syahrur Rohman Wahid; Mohammad Ali; Muh. Nur Rochim Maksum (CV. Rayyan Dwi Bharata, 2022)
Advanced Islamic education is a reconstruction of education that seeks to function as optimally as possible in religious life, practice experiences and actual problems in education and is able to anticipate change by thinking projectively (visionary) and acting proactively. John Dewey's educational theory of progressivism which is the basis for progressive education has the characteristics of progressivism, namely experience, intelligence and progress, so it is important to conduct a study on the implementation of the three pillars of advanced education in educational institutions. This research is classified as a qualitative descriptive research. This type of research is a field research with MI Muhammadiyah Gonilan and SDIT Muhammadiyah Al Kautsar Kartasura as a case study or research place. This data collection method is carried out by observation, interviews and documentation, while the data analysis is carried out interactively which begins with data reduction, data presentation and conclusion drawing. The results of the study indicate that the implementation of the three pillars of advanced Islamic education is indicated by special characters in schools, namely smart schools, learning experiences and education for sustainable development. Smart school is done by optimizing human reason or thinking ability by balancing science and religion. Experience makes experience a valuable lesson for educational progress, and education for sustainable development shows that advanced education continues to develop to continue to develop and move forward in the realities of social life.